Mapping Trends in Pedagogical Approaches and Learning Technologies: Perspectives from the Canadian, International, and Military Education Contexts - Scoppio, Grazia; Covell, Leigha (Canadian Journal of Higher Education, 2016)
Increased technological advances, coupled with new learners’ needs, have created new realities for higher education contexts. This study explored and mapped trends in pedagogical approaches and learning technologies in postsecondary education and identified how these innovations are affecting teaching and learning practices in higher education settings, particularly for the Canadian Armed Forces education system. A qualitative research methodology was employed including a comprehensive review of Canadian and international literature, an environmental scan of Canadian Armed Forces educational institutions, and consultations with experts and practitioners in the field of military education. The research findings shed light on trends in pedagogies and learning technologies in higher education as well as on the presence of these trends in the military educational system. In addition, the findings consider the necessity for a corresponding level of preparedness to meet the needs of diverse learners in the future. This study informs both the field of higher education and the field of military education.